Determinants of financial recording behavior in MSMEs: The role of digital accounting literacy, self-efficacy, mental accounting, and financial discipline - Novi Handayani Simbolon; Zulaikha Rahimah; Amelia Novizar; Arlina Pratiwi Purba (International Journal of Applied Finance and Business Studies, 2026)
This research investigates why MSME owners differ in their willingness to maintain systematic financial records. Using a behavioral accounting perspective, the study links digital accounting literacy, self-efficacy, mental accounting, and financial discipline to financial recording behavior. Data were obtained from 212 MSME owners and managers and processed using Partial Least Squares Structural Equation Modeling. The findings show that digital accounting literacy, self-efficacy, and mental accounting strengthen financial discipline and directly improve financial recording behavior. Financial discipline also becomes the strongest predictor of recording behavior and mediates the effects of the three antecedent variables. The model explains 58.7% of financial discipline and 68.4% of financial recording behavior. These results suggest that MSME bookkeeping practice depends not only on accounting knowledge or digital tools, but also on confidence, money separation habits, and repeated financial routines.